Takayasu's arteritis is associated with HLA-B*52, but not with HLA-B*51, in Turkey - DİRESKENELİ, RAFİ HANER (BIOMED CENTRAL LTD, 2012)
Introduction: HLA-B*51 and HLA-B*52 are two close human leukocyte antigen (HLA) allele groups with minor amino acid differences. However, they are associated with two different vasculitides (HLA-B*51 in Beh et's disease and HLA-B*52 in Takayasu's arteritis (TAK)) and with major clinical and immunological differences. In this study, we aimed to screen a large cohort of TAK patients from Turkey for the presence of HLA-B*51 and HLA-B* 52 as susceptibility and severity factors. Methods: TAK patients (n = 330) followed at a total of 15 centers were included in the study. The mean age of the patients was 37.8 years, and 86% were women. DNA samples from the patients and healthy controls (HC; n = 210) were isolated, and the presence of HLA-B* 51 or HLA-B* 52 was screened for by using PCR with sequence-specific primers. Results: We found a significant association of HLA-B* 52 with TAK (20.9% vs HC = 6.7%, P = 0.000, OR = 3.7, 95% CI = 2.02 to 6.77). The distribution of HLA-B* 51 did not differ between TAK patients and HCs (22.7% vs 24.8%, OR = 0.9, 95% CI = 0.60 to 1.34). The presence of HLA-B* 52 decreased in late-onset patients (> 40 years of age; 12.0%, P = 0.024, OR = 0.43, 95% CI = 0.20 to 0.91). Patients with angiographic type I disease with limited aortic involvement also had a lower presence of HLA-B* 52 compared to those with all other disease subtypes (13.1% vs 26%, P = 0.005, OR = 0.43, 95% CI = 0.23 to 0.78). Conclusions: In this study, the previously reported association of TAK with HLA-B* 52 in other populations was confirmed in patients from Turkey. The functional relevance of HLA-B* 52 in TAK pathogenesis needs to be explored further.
Keywords: GIANT-CELL ARTERITIS; HLA-B ALLELES; MHC CLASS-I; BEHCETS-DISEASE; CLINICAL-MANIFESTATIONS; GENE POLYMORPHISM; AORTIC TISSUE; CLASSIFICATION; SUSCEPTIBILITY; ANTIGENS